Ganges River Dolphin (Platanista gangetica gangetica): An Indicator of Ecosystem Health in the River Basins - Ranjan , Devarshi; Verma , Priyanka; Maurya , Preeti; Iqbal , Gowhar; Singh , Mayank Bhushan; Upadhyay , Aditya Kumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Along with turtles, crocodiles, and a few different species of sharks, the Ganges river dolphin (Platanista gangetica gangetica) is one of the oldest animals on the planet. The Ganges and Brahmaputra river basins in India, Nepal, and Bangladesh are home to this species. It generally lives in countercurrent systems of the main river channel and feeds mostly on fish. The Gangetic river dolphin is considered important because it acts as an indicator of the health of the overall river ecosystem. It was designated as the National Aquatic Animal of India on 5 October 2009. This species is now extinct in most of the areas where it once existed, due to serious threats from water development projects, pollution, poaching, and deaths from accidental entanglement in fishing gear. Currently, their population is estimated to be less than 2000 individuals. The Ganges river dolphin comes under Schedule I of the Wildlife Protection Act (1972). They are classified as Endangered in the IUCN Red List and included in CITES Appendix I. The Wildlife Institute of India launched an initiative called "Development of a Conservation Action Plan for Dolphins" in 2016 with the intention of saving these endangered dolphins.